FEATURE CHECKING AND SILENT NOUNS IN BRAZILIAN PORTUGUESE NOMINAL AGREEMENT - Pereira, Bruna Karla (Estudos Linguísticos e Literários, 2024)
This paper presents a work on nominal concord in Brazilian Portuguese (BP) structures, such as the following: (ia) “10 ovos caipira vermelhos” (10 egg-PL caipira red-PL / ‘10 red pasture-raised eggs’) and (ia’) “10 ovos [(do TIPO) caipira] vermelhos” (10 egg-PL (of-the TYPE) caipira red-PL / ‘10 red pasture-raised eggs’). Most of the data were collected from written sources that require the use of standard language concerning agreement, id est, the redundant plural marking in the constituents of the DP able to bear inflection. That is why the morpheme -s is marked in ovos and vermelhos (ia). Being so, why is the word caipira (ia) unmarked with the plural morpheme? Following Kayne’s (2005, 2019, 2021a, 2021b), Pesetsky’s (2007, 2013), Höhn’s (2016), and Pereira’s (2016a, 2016b, 2017, 2018, 2020, 2024) approach on structures with apparent mismatch of agreement, I argue that (ia) licenses a silent noun TIPO (TYPE), preceded by the preposition de (‘of’), as illustrated in (ia’). Therefore, caipira is inflected in singular, because it agrees in number with a singular silent noun. This analysis also applies to other structures that license the silent nouns TAMANHO (SIZE), TOM (HUE), and SOBRENOME (SURNAME). As a result, there is no “unagreement”, in the phrases at stake, but agreement between the adjective and a silent noun, in the DP-internal cartography.